Penerapan Kebijakan Aset Tetap dengan PSAP No. 07 pada Kantor Desa - Alivy Dinda Deviana; Norita Citra Yuliarti; Astrid Maharani (BUDGETING : Journal of Business, Management and Accounting, 2022)
The purpose of this study was to determine the treatment of fixed assets in Darungan Village, Tanggul District, Jember Regency on transactions related to the Fixed Assets Building Account. Furthermore, to find out the application of PSAP No. 07 regarding accounting for fixed assets of buildings that have been carried out in Darungan Village, Tanggul District, Jember Regency. This research method is qualitative research. Data were collected by means of a preliminary survey, interviews and documentation. The results of this study indicate that the competence of Human Resources (HR) in the accounting field is still limited and also Darungan Village, Tanggul District, Jember Regency has not depreciated fixed assets. In conclusion, Darungan Village, Tanggul District, Jember Regency does not yet have an accounting policy regarding Building Fixed Assets, so Darungan Village, Tanggul District, Jember Regency has not implemented PSAP No.07 in its entirety. Keywords: Building Fixed Assets, Qualitative, PSAP No.07